Prevalence of Bullying among Primary School Pupils in Al-Najaf City, Iraq - Essam Abed AL-Shibli; maytham ALnasrawii (Al-Anbar Medical Journal)
Background: Bullying is a harmful behavior that involves repeated aggressive actions intended to cause harm or distress to an individual. It is a major public health concern affecting children and adolescents. There is no local relevant study regarding this issue.Objectives: To determine the prevalence of bullying in primary schools.Materials and Methods: A cross-sectional study was carried out from 1st September 2023 to the 10th of April 2024 for a sample consisting of 1216 pupils. The sample of the present study was a group of pupils in fifth and sixth primary school classes for both sexes; those were found in the selected schools out of 201 schools currently found at Al-Najaf city, Iraq. The data collecting tools were direct interviews with the participants and a questionnaire composed of two parts, the first consisting of the demographic characteristics data and the second being the bullying items among primary school pupils.Results: The prevalence of bullying was 81.7%. The study shows 3.5% bullyer, 37.3% bullied, 41% bullyer/victim, and 18.3% were non-victims non bullyer. With the exception of the number of close friends in class, all other items were related to (P-value < 0.05) the prevalence of bullying roles (bullyer, bullied, and bullyer/victim).Conclusion: The study found a high prevalence of bullying among primary school students in Najaf City, which is concerning. An inverse relationship between protective factors and the prevalence of bullying has been identified. To address this, teachers should dedicate class time to discussing the harms of bullying and promote tolerance, while also supporting strategies to reduce school violence.